The Efficacy of Eccentric Training Versus Concentric Training Along With Therapeutic Ultrasound Therapy for Pain and Functioning in Subjects with Lateral Epicondylitis. - Misquitta, Chenessa; Prabhakar, Ronald (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Lateral Epicondylitis is a disabling musculoskeletal condition leading to pain and/or tenderness around the elbow. A common presentation may show pain and tenderness over the lateral epicondyle of the humerus, the radial head, the fascia, between the origins of extensor muscles as well as radiating into the forearm. Materials & Methodology: Patients with Lateral Epicondylitis (n=20) were included in this study and patients with fracture of upper limb, radiculopathies, undergoing steroid therapy, rheumatoid arthritis were excluded from the study. A comparative study was done where two groups were made, Group A (n=10) received Eccentric exercise along with Ultrasound Therapy and Group B (n=10) received Concentric exercise along with Ultrasound Therapy. Treatment was given for 3 times a week for 3 weeks. Pain was assessed using Numerical Pain Rating Scale and functional disability was assessed using Patient Rated Tennis Elbow Evaluation. Results: Group A showed significant decrease in pain and functioning as compared to Group B. Mean pre NPRS of eccentric subjects was 6.70 which was significantly higher than mean post NPRS 6.30 (p<0.001). Mean pre NPRS of concentric subjects was 6.30 which was significantly higher than mean post NPRS 2.60 (p<0.001). Mean pre PRTEE of eccentric subjects was 53.90 which was significantly higher than mean post PRTEE 12.85 (p<0.001). Mean pre PRTEE of concentric subjects was 55.45 which was significantly higher than mean post PRTEE 23.50 (p<0.001) Conclusion: The study concluded that Eccentric exercise along with Ultrasound Therapy is more effective than Concentric exercise along with Ultrasound Therapy.